BAHASA JAWA DALAM KETOPRAK HUMOR RCTI (SUATU TINJAUAN SOSIOLINGUISTIK) Javanese in Ketoprak Humor RCTI (A Sociolinguistic Prespective) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT This thesis is a descriptive study of the language used in Ketoprak Hu¬mor from sociolinguistic perspectives. Ketoprak Humor is a drama programme which is broadcasted weekly by the national television of RCTI. This programme is adopted from Ketoprak, a Javanese traditional performing art, which is originally conducted in Javanese. The language used in Ketoprak Humor, however, is not Javanese anymore. This programme mainly uses In¬donesian, but in some cases the using of Javanese cannot be avoided. Code switching and code mixing between Indonesian and Javanese often occur in Ketoprak Humor and the study is focused on it. The goals of this study are: (i) to describe linguistic forms of Javanese which are used in Kethoprak Humor, (ii) to identify determinant factors of the using of Javanese in Ketoprak Humor, (iii) to identify types of code switching and code mixing in Ketoprak Humor, and (iv) to explain functions and rea¬sons of code switching and code mixing in Ketoprak Humor. In providing data, the programmes of Ketoprak Humor in the television are recorded using tape recorder. The data, then, are transcribed on papers. After that, the transcriptions are analysed using contextual methods. In Ketoprak Humor, Javanese is mainly used by the jokers when they try to make a joke. In others occasion, however, especially when there is no Indonesian expression that can be used aply, some Javanese expression are also used. The Javanese linguistic forms that are often used in Kethoprak Humor include the terms of address, pronouns, swearwords, sorigs, frozen expression, emotional words, particles, affixes on verbs, respect words, etc. The types of code switching that are found in Ketoprak Humor include inter¬nal code switching, external code switching, temporal code switching, situ-ational code switching, metaphoric code switching, code switching with high frequency, and code switching with low frequency. There are many reasons for the occurring of code switching in Ketopmk Humor, among others thing, the language of the speakers or actors is Javanese, the presence of a third person, the topic of conversation, the influence of utterance that pre¬cede, and the goals of conversation. Meanwhile, code switching in Ketoprak Humor functions to make a joke, to make a language game, to express an annoyance, to threaten the other participant in conversation, to make a ridi¬cule, to show a social status, to curse, to express what the speaker is thinking about, and to copy utterances spoken by others. The linguistic units that are found in Ketoprak Humor include words, phrases, clauses, hybrid words, and others expression forms or idioms. The code mixing in Ketoprak Humor is underlay by the goals of conversation such as to show a respect, to show regional aspects, to give emphasis, and because of the influence of topic conversation and regional language.